Determining the PM10 Pollution Sources near the Copper Smelter in Bor, Serbia - Renata Kovačević; Bojan Radović; Dragan Manojlović; Tamara Urošević; Tatjana Apostolovski-Trujić; Viša Tasić; Milena Jovašević-Stojanović (Atmosphere)
The EPA Positive Matrix Factorization (PMF) 5.0 model was applied to determine the sources and characteristics of PM10 collected near the copper smelter in Bor, Serbia, from September 2009 to July 2010. For a better understanding of the industrial sources of PM10 pollution, the dataset was divided into four observation periods: heating season (HS), non-heating season (NHS), copper smelter in work (SW), and copper smelter out of work (SOW). The daily limit for the PM10 fraction of 50 μg/m3 was exceeded on one-sixth of days in the NHS, about half the days in the HS, and about one-third of days during the SOW and SW period. The nine different sources of PM10 were identified: fuel combustion, industrial dust, dust from tailings, storage and preparation of raw materials, secondary nitrate, Cu smelter, traffic, cadmium, and plant for the production of precious metals. The contribution of factors related to the activities in the copper smelter complex to the total mass of PM10 was 83.1%. When the copper smelter was out of work the contribution of all the factors related to PM10 pollution from the copper smelter to the total mass of the PM10 was 2.3-fold lower, 35.8%, compared with the period when the copper smelter was in work. This study is the first attempt to use PMF receptor modeling to determine the air pollution sources and their contribution to ambient air pollution in the city of Bor, Serbia.